“Ríos de aves” sobre Ciudad de Panamá (2007)
This article provides specific results about the research conducted by various scientists from the Smithsonian Tropical Research Institute for over twenty years, in relation with some of the birds migrating from the United States to Argentina across the Panama isthmus, focusing primarily on three birds of prey: the Turkey Vulture (Cathartes aura), the Broad-winged Hawk (Buteo platypterus), and the Swainson’s Hawk (Buteo swainsoni), all of which migratetheir way through a biological corridor that stretches along Panama’s pacific coast, including Panama City.